REMOVAL OF KEROSENE FROM WASTE WATER USING IRAQI BENTONITE - Abbas H. Sulaymon; Ziad T. Abd Ali (Journal of Engineering, 2010)
The aim of the present research is to study the potentiality of Iraqi bentonite as adsorbent for removing of kerosene from wastewater. Also the capacity of bentonite for kerosene removal was compared to the activated carbon capacity. The sorption of kerosene onto bentonite and AC. were described by two well – known adsorption isotherm models namely Langmuir and Freundlich models. It was found that the Freundlich model can fit very well the equilibrium isotherm adsorption of kerosene onto bentonite and AC. Batch experiments were carried out to study the effect of adsorption of kerosene onto bentonite using various conditions such as initial concentrations of kerosene ( 100-500 ) mg/L, agitation speeds (125, 250, 500, 800) RPM, and weights of bentonite ( 0.05, 0.5,1.1 ) gm, particle sizes (0.5- 0.6) mm, and temperature 303 k . It was found that the best results for removing kerosene onto bentonite were obtained at Co=500 mg/L, RPM =800. Activated carbon was used as powder and granular of particle sizes ranged (1-1.18) mm and (0.5-0.6) mm. The results indicated that the activated carbon was more active than bentonite for removing of kerosene from wastewater